2015
DOI: 10.1038/bjc.2015.198
|View full text |Cite
|
Sign up to set email alerts
|

Increasing incidence of base of tongue cancers from 2000 to 2010 due to HPV: the largest demographic study of 210 Danish patients

Abstract: Background:We assessed the development in the number of new base of tongue squamous-cell carcinoma (BSCC) cases per year in eastern Denmark from 2000 to 2010 and whether HPV may explain any observable increased incidence.Methods:We performed HPV DNA PCR and p16 immunohistochemistry analysis for all (n=210) BSCCs registered in the Danish Head and Neck Cancer Group (DAHANCA) and the Danish Pathology Data Bank, and genotyped all HPV-positive specimens with amplicon-based next-generation sequencing.Results:The ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 12 publications
(22 reference statements)
1
36
0
Order By: Relevance
“…This was most recently documented in two large Danish studies, which showed increasing proportions of HPV-positive tonsillar carcinoma and carcinomas at the base of the tongue between 2000 and 2010 (estimated annual percentage change 4.9% and 8.1%, respectively) [4,5]. If this increase in HPV prevalence has been higher among men than women and among younger than older individuals, it would support our finding of a greater decrease in mortality among male patients and younger patients with strongly HPV-associated HNSCC.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…This was most recently documented in two large Danish studies, which showed increasing proportions of HPV-positive tonsillar carcinoma and carcinomas at the base of the tongue between 2000 and 2010 (estimated annual percentage change 4.9% and 8.1%, respectively) [4,5]. If this increase in HPV prevalence has been higher among men than women and among younger than older individuals, it would support our finding of a greater decrease in mortality among male patients and younger patients with strongly HPV-associated HNSCC.…”
Section: Discussionmentioning
confidence: 76%
“…The known risk factors for HNC include tobacco smoking, alcohol drinking, and certain viruses, such as the Epstein-Barr virus and human papillomavirus (HPV) [1,2]. Increase in exposure to HPV over the past few decades have been shown to influence the incidence of certain HNSCCs with significant increases of some HNSCCs, such as those of the oropharynx, especially the tonsil and base of the tongue [3][4][5]. In Denmark, an overall increase in the incidence of HNSCC has been reported, due primarily to an increased incidence of cancers at sites reported to be associated with HPV [3].…”
Section: Original Articlementioning
confidence: 99%
“…This may cause a delay or result in a failure to reach the right diagnosis. In the past decade in Denmark, there has been an increasing incidence of patients with HPV‐positive OPSCC . It is well established that the predominant location of HPV‐positive OPSCC is the tonsillar crypts of the palatine tonsils or the base of the tongue .…”
Section: Introductionmentioning
confidence: 99%
“…Tongue squamous cell carcinoma (TSCC) is one of the most aggressive types of head and neck squamous cell carcinomas (HNSCC) with poor prognosis [47]. The outcome shows a selective participation of c-Jun with Fra-2/c-Fos to promote aggressive tumour phenotypes [48].…”
Section: Activator Protein-1mentioning
confidence: 99%